Materialities in innovative education: Focus on small Italian schools - Jose Mangione, Giuseppina Rita; Calzone, Samuele (Epistemological Approaches to Digital Learning in Educational Contexts, 2020)
The educational debate about digital uses in school-making changes revolves around the so-called material approaches. These approaches put materials in the foreground by moving research focus towards both educational practice and the multiple relationships occurring between subjects and objects of educational culture (paper documents, diaries, desks, chairs, workspaces, furniture, etc.) within teaching contexts. This work aims to explore the way digitally mediated materialities may support teaching practice in specific environments, such as small schools, whose educational context faces high risk of students drop-out and problems of weakness and inequality. Our analysis focuses on the digital learning materials adopted by a number of Italian small schools participating in Programma Operativo Nazionale (PON) per la Scuola – Competenze ed ambienti per l’apprendimento 2014–2020 (National Operational Programme for School – Skills and learning environments), to contrast drop-out. After a general analysis, the work will propose an insight into the above-mentioned small schools, with particular attention to those adhering to the Movimento delle Piccole Scuole (Small Schools Movement) and actively involved in the PON. This will help us understand how, in a particular educational context, digitally supported didactic materiality can be embedded in educational processes for achieving specific results.